2008
DOI: 10.1007/s10164-008-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic parameters of begging calls indicate chick body condition in Wilson’s storm-petrels Oceanites oceanicus

Abstract: Begging behaviour as a key element in the parent-offspring conflict has been studied in many avian species. These types of studies have nearly exclusively been based on call counts, and it is still not entirely clear whether begging calls themselves contain any information. We studied begging behaviour in Wilson's storm-petrel Oceanites oceanicus, a small procellariiform seabird. This species provides the opportunity to study the signalling value of begging calls in the absence of potentially confounding facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…While some previous studies have found acoustical parameters of begging call elements to be important in parent-chick interactions (Barn Swallows: Sacchi et al 2002), or to contain at least additional information (Wilson's Storm-Petrels: Gladbach et al 2009), another study did not find evidence that acoustic features of call elements are involved in the information exchange (Cory's Shearwaters: Träger et al 2006). In the latter study, no acoustic features of call elements correlated with body condition.…”
Section: Does Acoustic Structure Of Begging Call Elements Encode Infomentioning
confidence: 82%
See 4 more Smart Citations
“…While some previous studies have found acoustical parameters of begging call elements to be important in parent-chick interactions (Barn Swallows: Sacchi et al 2002), or to contain at least additional information (Wilson's Storm-Petrels: Gladbach et al 2009), another study did not find evidence that acoustic features of call elements are involved in the information exchange (Cory's Shearwaters: Träger et al 2006). In the latter study, no acoustic features of call elements correlated with body condition.…”
Section: Does Acoustic Structure Of Begging Call Elements Encode Infomentioning
confidence: 82%
“…% observations % calls in 1st session changes in acoustic begging call parameters (Gladbach et al 2009), suggesting a minor importance of this component of the begging signal.…”
Section: Does Acoustic Structure Of Begging Call Elements Encode Infomentioning
confidence: 99%
See 3 more Smart Citations